Sociology and Religions. An Ambiguous Relationship - Voy (KADOC-Studies, 1999)
What are the relations between sociology and the different religions - Christianity with its various branches, Judaism, Islam, Oriental religions, sects and New Religious Movements ? That is the question which this work, - conceived on the occasion of the XXVth Conference of the International Society for the Sociology of Religion/Soci